Organizational Culture as A Determinant of Effective Leadership in Elementary Schools - Ati, Hesti Mustika; Fachrial, Nur Fadli Hazhar; Sari, Bermara Giri Menur; Rahmani, Sofia F (Jurnal Manajemen Pendidikan, 2025)
Background In Indonesia, only 58% of principals meet managerial competency standards, fostering a supportive culture is essential to bridge leadership gaps and align with national education goals. Purpose This study explores how organizational culture enhances the performance effectiveness of elementary school principals, focusing on core values like collaboration, innovation, and inclusivity. Design/method/approach A qualitative case study design was employed, with data collected through semi-structured interviews involving principals and teachers from diverse elementary schools. Purposive sampling ensured representation of urban and rural contexts. Thematic analysis identified patterns in cultural practices and their impact on leadership effectiveness. Results Organizational culture, characterized by trust and shared decision-making, plays a crucial role in enhancing principal performance by fostering motivation and minimizing resistance to change. In this context, principals function as “cultural architects,” employing transformational leadership practicessuch as mentoring and participatory meetings to instill and strengthen core values within the school environment. However, contextual challenges, including resource disparities, demand adaptive cultural strategies, particularly in rural schools where emphasizing mutual cooperation becomes essential for sustaining progress and achieving shared goals. Contribution/value The study contributes by highlighting how organizational culture grounded in trust and shared decision-making significantly enhances principal performance through transformational leadership practices.